The Poverty Reduction Strategy Approach Six Years On: An Examination of Principles and Practice in Uganda - Canagarajah, Sudharshan; van Diesen, Arthur (2012)
It is over six years since the World Bank and the IMF started promoting a PRS approach to development management in low-income countries. The 2005 review endorsed the approach, but highlighted the need for a renewed focus on the principles underpinning it: country ownership; results orientation; comprehensiveness; partnership focus; and long-term outlook. Uganda is often hailed as one of the best PRS performers. This article finds that Uganda's Poverty Eradicaton Action Plan (PEAP) has brought significant gains to development management, but that its performance against several of the PRS principles is disappointing. A return to these principles could improve the practice of the government and development partners around the PEAP--a finding likely to be applicable to many countries implementing a PRS.